1987
DOI: 10.1002/ajmg.1320260413
|View full text |Cite
|
Sign up to set email alerts
|

Dominantly inherited renal adysplasia

Abstract: We are reporting on 7 families with both unilateral and bilateral renal agenesis (or severe dysplasia). This condition, termed hereditary renal adysplasia (HRA) [Buchta et al, 1973], is an autosomal dominant trait with incomplete penetrance and variable expression. Review of the literature on familial renal agenesis suggests that HRA is more common than previously supposed and may account for most recurrences of bilateral renal agenesis (BRA), even when the parents are normal. There are no consistent phenotypi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
46
0
2

Year Published

1996
1996
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 112 publications
(49 citation statements)
references
References 28 publications
1
46
0
2
Order By: Relevance
“…1,[3][4][5][6] For familial cases, the suggested mode of inheritance in most pedigrees is autosomal dominant with variable expression and reduced penetrance, estimated to range between 50% and 90%. 7 The pathologic basis of RHD is the disturbance of normal nephrogenesis, possibly due to mutations in genes that direct the process. 1,8 Most of the genes known to be involved are transcriptional factors and genes that encode for proteins involved in the mesenchymal to epithelial transition.…”
mentioning
confidence: 99%
“…1,[3][4][5][6] For familial cases, the suggested mode of inheritance in most pedigrees is autosomal dominant with variable expression and reduced penetrance, estimated to range between 50% and 90%. 7 The pathologic basis of RHD is the disturbance of normal nephrogenesis, possibly due to mutations in genes that direct the process. 1,8 Most of the genes known to be involved are transcriptional factors and genes that encode for proteins involved in the mesenchymal to epithelial transition.…”
mentioning
confidence: 99%
“…Approximately 1000 UK children have end-stage renal failure, and in approximately half of these individuals, the cause is a congenital abnormality of both kidneys (2), usually renal dysplasia, in which kidneys begin to form but contain undifferentiated and metaplastic tissues, sometimes with cysts (3). Some such organs spontaneously involute to give an aplastic phenotype (4,5), and therefore a spectrum of anomalies is recognized, called renal "adysplasia" (6,7). Severe bilateral renal adysplasia occurs in approximately one in 10,000 births (3).…”
mentioning
confidence: 99%
“…Perhaps multiple genes interact to generate the anomaly: Indeed, Nishimura et al (19) found an association with a common polymorphism of the angiotensin II receptor type 2 (AT2) gene with diverse urinary tract malformations; however, this could not be replicated (20). In rare families with more than one affected individual, renal adysplasia might have a dominant inheritance with reduced penetrance and variable expressivity (6,7,21). Our hypothesis to explain the sporadic occurrence of bilateral renal adysplasia is that such individuals have de novo dominant mutations of genes expressed in renal tract differentiation; because such individuals would often have severe renal failure, they would not generally have lived to reproduce in the era before the advent of modern dialysis and transplantation.…”
mentioning
confidence: 99%
“…Furthermore, it allowed identification of families in which affected relatives might have different types of renal disease, such as the previously described hereditary renal adysplasia, in which renal agenesis, hypoplasia, dysplasia, and cystic dysplasia have all been reported. [17][18][19][20] The observation that concordance for the precise type of renal anomaly was only approximately 50% among relatives suggests that many families would have been missed if the study had been limited to renal agenesis.…”
Section: Discussionmentioning
confidence: 99%
“…The occurrence of bilateral renal agenesis in these families, however, is much less than expected given previous estimates of the penetrance for bilateral renal agenesis and unilateral renal agenesis, each approximately 33% in hereditary renal adysplasia heterozygotes. 19 Either previous estimates are biased because of ascertainment of hereditary renal adysplasia through bilaterally affected probands, or a significant number of unilateral renal agenesis recurrences are the result of some other cause. In any case, it is reassuring for counseling purposes that the empiric risk for bilateral renal agenesis in offspring of congenital solitary kidney probands is only approximately 1%, rather than the 15% to 20% predicted for hereditary renal adysplasia heterozygotes.…”
Section: Discussionmentioning
confidence: 99%